Intelligence science and big data engineering : 8th International Conference, IScIDE 2018, Lanzhou, China, August 18-19, 2018, Revised selected papers /: 8th International Conference, IScIDE 2018, Lanzhou, China, August 18-19, 2018, Revised selected papers. (2018) - Unknown
No abstract available